Effectiveness of pre-entry active tuberculosis and post-entry latent tuberculosis screening in new entrants to the UK: a retrospective, population-based cohort study. Issue 11 (November 2019) - Berrocal-Almanza, Luis C; Harris, Ross; Lalor, Maeve K; Muzyamba, Morris C; Were, John; O'Connell, Anne-Marie; Mirza, Adil; Kon, Onn-Min; Lalvani, Ajit; Zenner, Dominik
Summary: Background: Evaluating interventions that might lead to a reduction in tuberculosis in high-income countries with a low incidence of the disease is key to accelerate progress towards its elimination. In such countries, migrants are known to contribute a large proportion of tuberculosis cases to the burden. We assessed the effectiveness of screening for active tuberculosis before entry to the UK and for latent tuberculosis infection (LTBI) post-entry for reduction of tuberculosis in new-entrant migrants to the UK. Additionally, we investigated the effect of access to primary care on tuberculosis incidence in this population. Methods: We did a retrospective, population-based cohort study of migrants from 66 countries who were negative for active tuberculosis at pre-entry screening between Jan 1, 2011, and Dec 31, 2014, and eligible for LTBI screening. We used record linkage to track their first contact with primary care, uptake of LTBI screening, and development of active tuberculosis in England, Wales, and Northern Ireland. To assess the effectiveness of the pre-entry screening programme, we identified a control group of migrants who were not screened for active tuberculosis using the specific code for new entrants to the UK registering in primary care within the National Health Service patient registration data system. Our primary outcome was development of active tuberculosis notified to the National Enhanced Tuberculosis Surveillance System. Findings: Our cohort comprised 224 234 migrants who were screened for active tuberculosis before entry to the UK and a control group of 118 738 migrants who were not. 103 990 (50%) migrants who were screened for active tuberculosis registered in primary care; all individuals in the control group were registered in primary care. 1828 tuberculosis cases were identified during the cohort time, of which 31 were prevalent. There were 26 incident active tuberculosis cases in migrants with no evidence of primary care registration, and 1771 cases in the entire cohort of migrants who registered in primary care (n=222 728), giving an incidence rate of 174 (95% CI 166–182) per 100 000 person-years. 672 (1%) of 103 990 migrants who were screened for active tuberculosis went on to develop tuberculosis compared with 1099 (1%) of 118 738 not screened for active tuberculosis (incidence rate ratio [IRR] 1·49, 95% CI 1·33–1·67; p<0·0001). 2451 (1%) of the 222 728 migrants registered in primary care were screened for LTBI, of whom 421 (17%) tested positive and 1961 (80%) tested negative; none developed active tuberculosis within the observed time period. Migrants settling in the least deprived areas had a decreased risk of developing tuberculosis (IRR 0·74, 95% CI 0·62–0·89; p=0·002), and time from UK arrival to primary care registration of 1 year or longer was associated with increased risk of active tuberculosis (2·96, 2·59–3·38; p<0·0001). Interpretation: Pre-entry tuberculosis screening, early primary care registration, and LTBI screening are strongly and independently associated with a lower tuberculosis incidence in new-entrant migrants. Funding: National Institute for Health Research (NIHR) Health Protection Research Unit in Respiratory Infections and NIHR Imperial Biomedical Research Centre.